The impact of EEC financial assistance on Irish economic development since 1973 - McNamara, Brendan (Statistical and Social Inquiry Society of Ireland, 1984)
Ireland became a member of the European Economic Community on January 1 1973. The decision to join an enlarged EEC had many motives, political and economic. Among the most important was the belief that membership would contribute positively to the further development of the Irish economy both in terms of the stimulus it would give to investment and growth and, more directly, because of the flow of funds that we could expect to obtain from Europe. The purpose of the present paper is to assess how far financial assistance to Ireland from the Community has contributed to development of the economy. The analysis is intended to answer a number of questions: (I) how has Community financial assistance to Ireland grown since 1973? (ii) how has Ireland's share of the Community budget and of other finances developed as compared with our Community partners? (iii) what has been the relationship between EEC financing and: (a) development of the size and structure of the national budget (with particular emphasis on the capital budget); (b) investment growth?
Symposium on EEC Membership
Read before the Society, 30th May, 1984
Keywords: European Economic Community financing; Economic growth; 314.15